Preparation and application of metal oxide nanotube catalyst with confinement effect

The metal oxide nanotubes were prepared by hydrothermal method and loaded with precious metals by impregnation method, which solved the problem of active center aggregation and sintering of catalysts in the hydrogenation of CO2 to methanol reaction, and achieved optimization of catalyst performance and efficient utilization of precious metals.

CN119524842AActive Publication Date: 2025-02-28BEIJING UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411764010.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-28
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The existing catalysts have problems with active center aggregation and sintering in the CO2 hydrogenation and methanol reaction, resulting in poor performance, high loading of precious metals and high cost.

Method used

Metal oxide nanotubes with a limited domain effect were prepared by hydrothermal method, and noble metals were loaded into and out of the nanotube by impregnation method, and the dispersion of noble metals and the inner diameter of the support were controlled to improve catalytic performance.

Benefits of technology

The performance optimization of the catalyst is achieved. The performance of the catalyst supported by the precious metals in the tube is better than that of the catalyst supported by the precious metals outside the tube, which improves the anti-sintering ability of the catalyst and the utilization efficiency of the precious metals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524842A_ABST
    Figure CN119524842A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a metal oxide nanotube catalyst with confinement effect, and belongs to the field of catalyst preparation. The preparation method comprises the following steps: preparing a nanotube by adopting a hydrothermal method, and respectively loading noble metal into and out of the nanotube by adopting an impregnation method; the outer diameter of the nanotube is 20 to 300 nm, the wall thickness of the nanotube is 10 to 150 nm, and the length of the nanotube is 30 to 500 nm; the catalyst is composed of an active component and a carrier, the active component is a noble metal, the carrier is a nanotube, the nanotube is one of a CeO2 nanotube, a TiO2 nanotube and the like, and the noble metal is one of Pd, Ir, Rh and Ru; the content of the active component accounts for 0.1%-10% of the total mass of the catalyst, and the carrier accounts for 90%-99.9% of the total mass of the catalyst; the obtained catalyst is used for preparing methanol through CO2 hydrogenation, and by changing the position of the active component on the carrier, and due to the confinement effect of the nanotube, the performance of the catalyst loaded with the noble metal inside the nanotube is superior to that of the catalyst loaded with the noble metal outside the nanotube.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of a metal oxide nanotube catalyst with confinement effect and application thereof, belonging to the technical field of catalyst preparation. Background Art

[0002] The confinement effect is a concept first proposed in the field of catalysis and surface science, and is currently widely used in the field of catalyst preparation technology. In the process of catalyst preparation, the confinement effect can affect the number and distribution of active centers, and can also provide a chemical microenvironment for the nucleation and growth of crystals to obtain unique physical and chemical properties. Therefore, the confinement effect has been widely used in the synthesis of materials in the fields of hydrogen storage, sensing, catalysis, drug release and separation.

[0003] The confinement effect mainly includes interface confinement and pore confinement. Active centers loaded inside carbon nanotubes, core-shell catalysts, and metal oxide nanotubes are beneficial to the sintering resistance and reaction stability of the catalysts. Carbon nanotubes and core-shell catalysts have been widely studied, while the confinement effect of metal oxide nanotubes with hollow structures remains to be studied. Therefore, it is of great significance to explore the confinement effect of metal oxide nanotubes.

[0004] In the catalytic system, precious metals as active center catalysts have the advantages of high activity and good stability. If we can find a way to improve the activity of the catalyst and reduce the loading of precious metals, the cost of the catalyst will be greatly reduced and the application prospects of precious metal catalysts will be improved. The precious metals are combined with metal oxide nanotubes with confinement effect, and the precious metals are loaded inside and outside the metal oxide nanotubes respectively by a specific preparation method. The inner diameter of the metal oxide nanotubes limits the growth of the active metals inside the tubes, which can maximize its dispersion. It also hinders the aggregation of active center particles during the reaction process, improving the performance and anti-sintering ability of the catalyst. Applied to CO2 hydrogenation to methanol, the confinement effect of metal oxide nanotubes is used to make the performance of the precious metal loaded inside the catalyst tube better than that of the precious metal loaded outside the catalyst tube, thereby achieving performance optimization. Summary of the invention

[0005] In order to overcome the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a metal oxide nanotube catalyst with a confinement effect.

[0006] Another object of the present invention is to provide the use of the above-mentioned metal oxide nanotube catalyst with confinement effect in the hydrogenation of carbon dioxide to methanol.

[0007] The present invention provides a preparation method and application of a metal oxide nanotube catalyst with confinement effect, which is characterized in that the catalyst has a hollow tubular structure, the outer diameter of the nanotube is 20 to 300 nm, the wall thickness of the nanotube is 10 to 150 nm, the length of the nanotube is 30 to 500 nm, and the catalyst is composed of an active component and a carrier, wherein the active component is a noble metal and the carrier is a metal oxide nanotube; the active component is located inside or outside the tube on the carrier, the metal oxide nanotube has a confinement effect on the loaded active component, and the content of the active component accounts for 10% of the total mass of the catalyst. The catalyst is 0.1% to 10% of the total mass of the catalyst, and the carrier accounts for 90% to 99.9% of the total mass of the catalyst; it is applied to CO2 hydrogenation to methanol, and the performance is optimized by changing the position of the active component on the carrier and utilizing the confinement effect of the metal oxide nanotubes. The performance of the catalyst loaded with the precious metal inside the tube is better than that of the catalyst loaded with the precious metal outside the tube; the metal oxide nanotube is one of CeO2 nanotube, TiO2 nanotube, Fe2O3 nanotube, MnO2 nanotube, Al2O3 nanotube, and the precious metal is one of Pd, Ir, Rh, and Ru;

[0008] The method comprises the following steps:

[0009] (1) Preparation of metal oxide nanotubes: mixing a metal-containing precursor, a ligand and deionized water in a mass ratio of (1-50): (1-100): (40-200), performing a hydrothermal reaction at 120-220° C. for 10-48 hours, and after the reaction, performing solid-liquid separation, collecting the solid, washing and drying it, and calcining it at 300-750° C. for 2-6 hours to obtain metal oxide nanotubes;

[0010] (2) Impregnation method: Use precious metal precursors to load precious metals inside and outside the metal oxide nanotubes: Use vacuum-assisted stirring to load the precious metal precursors inside the nanotubes, and use ordinary stirring impregnation method to load the precious metal precursors outside the nanotubes, then dry and calcine at 300-700°C for 2-6 hours.

[0011] In one embodiment of the present invention, in step (1), the metal precursor is one of Ce(OH)CO3, titanium dioxide P25, FeCl3, KMnO4, Al(NO3)3·9H2O, and the ligand solution is one or more of NaOH, NH4H2PO4, HCl, hexadecyltrimethylammonium bromide, and urea.

[0012] In one embodiment of the present invention, in step (2), the noble metal precursor is a salt or acid of the noble metal Ir, Rh, Pd, Ru; specifically, it can be selected from any one or more of the following: H2PdCl4, H2IrCl6, K3RhCl6, (NH4)RuCl6, Na2IrCl6, the noble metal accounts for 0.1% to 10% of the total mass of the catalyst, and the metal oxide nanotubes account for 90% to 99.9% of the total mass of the catalyst.

[0013] The present invention also provides the use of any of the metal oxide nanotube catalysts with confinement effect described above in catalyzing the hydrogenation of carbon dioxide to produce methanol.

[0014] In one embodiment of the present invention, the catalyst does not need to be reduced, but is directly heated in the feed gas to start the reaction.

[0015] In one embodiment of the present invention, the reaction conditions for catalytic hydrogenation of carbon dioxide to produce methanol are: CO2 / H2=1:1-5, specifically 1:3; space velocity is 3-20 L / g cat / h, 3L / g is optional cat / h; the reaction temperature is 100-500°C, specifically 240°C; the reaction pressure is 0-5MPa, specifically 3MPa.

[0016] Compared with the shortcomings and deficiencies of the prior art, the present invention has the following beneficial effects:

[0017] The present invention can controllably prepare metal oxide nanotubes with confinement effect by a simple hydrothermal method, and then load the precious metal into the tube and outside of the nanotube by an impregnation method. This preparation method is simple and easy to implement. The precious metal is combined with the metal oxide nanotube with confinement effect, and the precious metal is loaded into the tube and outside of the metal oxide nanotube respectively by a specific preparation method. The inner diameter of the metal oxide nanotube limits the growth of the active metal in the tube, and its dispersion can be maximized. The aggregation of active center particles will also be hindered during the reaction process, and the performance and anti-sintering ability of the catalyst will be improved. It is applied to CO2 hydrogenation to methanol. Since the metal oxide nanotube has a confinement effect, the performance of the precious metal loaded in the catalyst tube is better than the performance of the precious metal loaded outside the catalyst tube, thereby achieving performance optimization. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 a is one of the transmission electron microscopy images of the catalyst prepared in Example 1. Figure 1 b is the second transmission electron microscopy image of the catalyst prepared in Example 1.

[0019] Figure 2 a is one of the transmission electron microscopy images of the catalyst prepared in Example 2. Figure 2b is the second transmission electron microscopy image of the catalyst prepared in Example 2. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0021] Catalyst performance evaluation: The catalytic carbon dioxide hydrogenation reaction in the following examples was carried out in a stainless steel fixed bed reactor. The specific catalytic performance test and evaluation method is as follows:

[0022] (1) 0.2 g of metal oxide nanotube catalyst was mixed with 0.4 g of quartz sand and placed in a reactor.

[0023] (2) The reaction gas (H2 / CO2=3 / 1) flows through the catalyst bed at a flow rate of 10 mL / min, and the reaction pressure gradually increases to the set pressure of 3 MPa, and the reaction temperature gradually increases to the set temperature of 240°C to start the reaction.

[0024] (3) The product directly enters the gas chromatograph for detection and analysis. The gas chromatograph is equipped with TCD and FID detectors. The TCD detector uses high-purity argon as the carrier gas and uses a sieve 5A stainless steel column to separate permanent gases such as H2, N2, CO2, CO, and CH4. The FID detector uses high-purity N2 as the carrier gas and uses two FID capillary columns, HP-Innowax and HP-AL / S. HP-AL / S is used to separate C1 to C5 hydrocarbons; HP-Innowax is used to separate C 6+ Alkanes, aromatics and oxygen-containing carbides.

[0025] CO2 conversion rate = (imported CO2 moles – export CO2 moles) / imported CO2 moles × 100%;

[0026] Product selectivity = number of moles of outlet product × number of carbon atoms in product molecules / (number of moles of inlet CO2 – number of moles of outlet CO2) × 100%.

[0027] The loading amount involved in the present invention refers to the mass fraction of the metal content of the active component to the total mass of the catalyst.

[0028] Example 1

[0029] (1) Dissolve 4.8 g of sodium hydroxide in 80 ml of deionized water, add 0.1 g of Ce(OH)CO3 precursor, mix well, put into a 200 ml polytetrafluoroethylene-lined stainless steel reactor, perform hydrothermal reaction at 120°C for 24 h, cool, wash and dry, and calcine at 450°C for 4 h to obtain CeO2 nanotubes.

[0030] (2) Pd was loaded into CeO2 nanotubes by vacuum-assisted stirring impregnation method: 1 g CeO2 nanotubes were placed in a three-necked flask, 0.0168 g H2PdCl4 was dissolved in 10 ml water and placed in a separatory funnel, the whole device was evacuated for 30 min, the separatory funnel was unscrewed, the solution and CeO2 nanotubes were mixed, stirred for 2 h, dried, and calcined at 550 °C for 5 h. Figure 1 a and Figure 1 b is a transmission electron microscope image of the catalyst prepared in this example. Figure 1 In a, it can be seen that the carrier cerium dioxide is a hollow nanotube structure with an outer diameter of 48nm and an inner diameter of 16nm. Figure 1 In b, it can be seen that Pd particles are loaded inside the CeO2 nanotubes.

[0031] Activity test: Referring to the aforementioned “Catalyst Performance Evaluation”, the catalytic activity of the prepared catalyst was evaluated in a fixed bed reactor. The activity test results are shown in Table 1.

[0032] Example 2

[0033] (1) Same as Example 1;

[0034] (2) Pd was loaded on the outside of CeO2 nanotubes by impregnation method. 0.0168 g H2PdCl4 was dissolved in 10 ml water, added to 1 g CeO2 nanotubes, stirred for 2 h, dried, and calcined at 550 °C for 5 h. Figure 2 a and Figure 2 b is a transmission electron microscope image of the catalyst prepared in this example. Figure 2 In a, it can be seen that the carrier cerium dioxide is a hollow nanotube structure with an outer diameter of 48nm and an inner diameter of 16nm. Figure 2 In b, it can be seen that Pd particles are loaded outside the CeO2 nanotubes.

[0035] Activity test: Referring to the aforementioned “Catalyst Performance Evaluation”, the catalytic activity of the prepared catalyst was evaluated in a fixed bed reactor. The activity test results are shown in Table 1.

[0036] Example 3

[0037] (1) Dissolve 48g NaOH in 120ml water and add 1g titanium dioxide P 25 , stirred for 30 min, the mixed solution was transferred to a 200 ml polytetrafluoroethylene-lined stainless steel reactor, and then hydrothermally treated at 180 ° C for 48 h, cooled, washed and dried, and calcined at 600 ° C for 2 h to obtain TiO2 nanotubes;

[0038] (2) Pd was loaded into TiO2 nanotubes by vacuum-assisted stirring impregnation method: 1 g TiO2 nanotubes were placed in a three-necked flask, 0.0168 g H2PdCl4 was dissolved in 10 ml water and placed in a separatory funnel, the entire device was evacuated for 30 min, the separatory funnel was unscrewed, the solution and TiO2 nanotubes were mixed, stirred for 2 h, dried, and calcined at 550 °C for 5 h.

[0039] Activity test: Referring to the aforementioned “Catalyst Performance Evaluation”, the catalytic activity of the prepared catalyst was evaluated in a fixed bed reactor. The activity test results are shown in Table 1.

[0040] Example 4

[0041] (1) Same as Example 3;

[0042] (2) Pd was loaded on the outside of TiO2 nanotubes by the impregnation method. 0.0168 g H2PdCl4 was dissolved in 10 ml water, added to 1 g TiO2 nanotubes and stirred for 2 h. The mixture was dried and calcined at 550 °C for 5 h.

[0043] Activity test: Referring to the aforementioned “Catalyst Performance Evaluation”, the catalytic activity of the prepared catalyst was evaluated in a fixed bed reactor. The activity test results are shown in Table 1.

[0044] Example 5

[0045] (1) 5.1 g FeCl3, 1.3 g NH4H2PO4 and 80 ml ultrapure water were mixed and placed in a 200 ml polytetrafluoroethylene-lined stainless steel reactor, and then hydrothermally treated at 220°C for 48 h, cooled, washed and dried, and calcined at 550°C for 5 h to obtain Fe2O3 nanotubes.

[0046] (2) Pd was loaded into Fe2O3 nanotubes by vacuum-assisted stirring impregnation method: 1 g of Fe2O3 nanotubes was placed in a three-necked flask, 0.0168 g of H2PdCl4 was dissolved in 10 ml of water and placed in a separatory funnel, the entire device was evacuated for 30 min, the separatory funnel was unscrewed, the solution and Fe2O3 nanotubes were mixed, stirred for 2 h, dried, and calcined at 550 °C for 5 h.

[0047] Activity test: Referring to the aforementioned “Catalyst Performance Evaluation”, the catalytic activity of the prepared catalyst was evaluated in a fixed bed reactor. The activity test results are shown in Table 1.

[0048] Example 6

[0049] (1) Same as Example 5;

[0050] (2) Pd was loaded on the outside of Fe2O3 nanotubes by impregnation method. 0.0168 g H2PdCl4 was dissolved in 10 ml water, added to 1 g Fe2O3 nanotubes and stirred for 2 h. The mixture was dried and calcined at 550 °C for 5 h.

[0051] Activity test: Referring to the aforementioned “Catalyst Performance Evaluation”, the catalytic activity of the prepared catalyst was evaluated in a fixed bed reactor. The activity test results are shown in Table 1.

[0052] Example 7

[0053] (1) 1.32 g KMnO4, 1.77 g concentrated HCl and 150 ml ultrapure water were mixed and stirred evenly, placed in a 200 ml polytetrafluoroethylene-lined stainless steel reactor, and then hydrothermally treated at 150°C for 10 h, cooled, washed and dried, and calcined at 550°C for 5 h to obtain MnO2 nanotubes.

[0054] (2) Pd was loaded into MnO2 nanotubes by vacuum-assisted stirring impregnation method: 1 g of MnO2 nanotubes was placed in a three-necked flask, 0.0168 g of H2PdCl4 was dissolved in 10 ml of water and placed in a separatory funnel, the entire device was evacuated for 30 min, the separatory funnel was unscrewed, the solution and MnO2 nanotubes were mixed, stirred for 2 h, dried, and calcined at 550 °C for 5 h.

[0055] Activity test: Referring to the aforementioned “Catalyst Performance Evaluation”, the catalytic activity of the prepared catalyst was evaluated in a fixed bed reactor. The activity test results are shown in Table 1.

[0056] Example 8

[0057] (1) Same as Example 7;

[0058] (2) Pd was loaded on the outside of MnO2 nanotubes by impregnation method. 0.0168 g H2PdCl4 was dissolved in 10 ml water, added to 1 g MnO2 nanotubes and stirred for 2 h. The mixture was dried and calcined at 550 °C for 5 h.

[0059] Activity test: Referring to the aforementioned “Catalyst Performance Evaluation”, the catalytic activity of the prepared catalyst was evaluated in a fixed bed reactor. The activity test results are shown in Table 1.

[0060] Example 9

[0061] (1) 7.504 g Al(NO3)3·9H2O, 7.288 g hexadecyltrimethylammonium bromide, 6.004 g CO(NH2)2 and 144 ml ultrapure water were mixed and stirred uniformly, placed in a 200 ml polytetrafluoroethylene-lined stainless steel reactor, and subjected to hydrothermal treatment at 125°C for 15 h, cooled, washed and dried, and calcined at 550°C for 5 h to obtain Al2O3 nanotubes.

[0062] (2) Pd was loaded into Al2O3 nanotubes by vacuum-assisted stirring impregnation method: 1 g Al2O3 nanotubes were placed in a three-necked flask, 0.0168 g H2PdCl4 was dissolved in 10 ml water and placed in a separatory funnel, the entire device was evacuated for 30 min, the separatory funnel was unscrewed, the solution and Al2O3 nanotubes were mixed, stirred for 2 h, dried, and calcined at 550 °C for 5 h.

[0063] Activity test: Referring to the aforementioned “Catalyst Performance Evaluation”, the catalytic activity of the prepared catalyst was evaluated in a fixed bed reactor. The activity test results are shown in Table 1.

[0064] Example 10

[0065] (1) Same as Example 9;

[0066] (2) Pd was loaded on the outside of Al2O3 nanotubes by impregnation method. 0.0168 g H2PdCl4 was dissolved in 10 ml water, added to 1 g Al2O3 nanotubes and stirred for 2 h. The mixture was dried and calcined at 550 °C for 5 h.

[0067] Activity test: Referring to the aforementioned “Catalyst Performance Evaluation”, the catalytic activity of the prepared catalyst was evaluated in a fixed bed reactor. The activity test results are shown in Table 1.

[0068] The results of the catalytic reaction are shown in Table 1. The results show that in the reaction of CO2 hydrogenation to methanol, for the same type of metal oxide nanotubes, whether it is the CO2 conversion rate or the methanol selectivity, the catalyst performance of the catalyst loaded with Pd inside the tube is higher than that of the catalyst loaded with Pd outside the tube, indicating that the metal oxide nanotubes have a confinement effect on the precious metal loaded inside the tube, and this confinement effect affects the metal-support interaction. The inner diameter of the metal oxide nanotube limits the growth of the active metal in the tube, which can maximize its dispersion and hinder the aggregation of active center particles during the reaction, thereby improving the performance and anti-sintering ability of the catalyst.

[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

[0070] Table 1 Reaction performance of different catalysts in the examples

Claims

1. A method for preparing a metal oxide nanotube catalyst having a confinement effect, characterized in that: The catalyst has a hollow nanotube structure, the outer diameter of the nanotube is 20 to 300 nm, the wall thickness of the nanotube is 10 to 150 nm, the length of the nanotube is 30 to 500 nm, and the catalyst is composed of an active component and a carrier, wherein the active component is a noble metal and the carrier is a metal oxide nanotube; the active component is located inside or outside the tube on the carrier, the active component content accounts for 0.1% to 10% of the total mass of the catalyst, and the carrier accounts for 90% to 99.9% of the total mass of the catalyst; the nanotube is one of CeO2 nanotube, TiO2 nanotube, Fe2O3 nanotube, MnO2 nanotube, Al2O3 nanotube, and the noble metal is one of Pd, Ir, Rh, and Ru; The method comprises the following steps: (1) Preparation of metal oxide nanotubes: a metal precursor, a ligand and deionized water are mixed in a mass ratio of (1-50): (1-100): (40-200), and a hydrothermal reaction is carried out at 120-220°C for 10-48 hours. After the reaction, the solid and liquid are separated, and the solid is collected, washed and dried, and calcined at 300-750°C for 2-6 hours to obtain metal oxide nanotubes; the metal precursor is one of Ce(OH)CO3, titanium dioxide P25, FeCl3, KMnO4, and Al(NO3)3·9H2O, and the ligand is one or more of NaOH, NH4H2PO4, HCl, hexadecyltrimethylammonium bromide, and urea; (2) Impregnation method: noble metal precursors are used to load noble metals inside and outside the metal oxide nanotubes: vacuum-assisted stirring is used to load the noble metal precursors inside the nanotubes, and stirring impregnation method is used to load the noble metal precursors outside the nanotubes, followed by drying and calcination at 300-700°C for 2-6h; The noble metal precursor is a salt or acid of noble metals Ir, Rh, Pd and Ru; the noble metal accounts for 0.1% to 10% of the total mass of the catalyst, and the metal oxide nanotubes account for 90% to 99.9% of the total mass of the catalyst.

2. The method according to claim 1, characterized in that: The noble metal precursor is selected from any one or more of the following: H2PdCl4, H2IrCl6, K3RhCl6, (NH4)RuCl6, Na2IrCl6.

3. Use the catalyst prepared by the method as claimed in claim 1.

4. Application of the catalyst prepared by the method according to claim 1 in catalytic hydrogenation of carbon dioxide to methanol.

5. The use according to claim 4, characterized in that: The reaction conditions for catalytic hydrogenation of carbon dioxide to produce methanol are: volume ratio CO2 / H2 = 1:1-5, space velocity 3-20L / g cat / h, the reaction temperature is 100-500°C, and the reaction pressure is 0-5MPa.

Citation Information

Patent Citations

  • Antibacterial functionalized artificial joint with silver-loaded nanotube array surface

    CN101766840A

  • Catalyst for synthesis of methanol by hydrogenation of carbon dioxide at normal pressure as well as preparation method and application thereof

    CN106311249A

  • Preparation and application of catalyst for preparing methanol through carbon dioxide hydrogenation

    CN110787789A

  • Preparation of thermally stable ALD modified specific crystal face CeO2 carrier loaded Pd three-way catalyst

    CN111468113A

  • Metal catalyst for preparing methanol through carbon dioxide hydrogenation and application of metal catalyst

    CN114950419A